Narrative as Memory: A Reading of Nuruddin Farah’s Trilogy Variations on the Theme of an African Dictatorship - Abdelhafez, Sarah Nagaty (2017)
The hallmark of the three novels forming Nuruddin Farah’s trilogy Variations on the Theme of an African Dictatorship is the fact that they share several tales of recurrent symbolic departure and return. This cyclical nature of Farah’s narrative foregrounds the collective traumatic past that Farah’s narrative embodies. In three chapters, the trilogy is analysed in the light of the writings of some Trauma Studies theorists such as Anne Whitehead, Cathy Caruth, Marianne Hirsch, and Dominick LaCapra. The first chapter examines the theoretical foundation of reading trauma in Farah’s narrative. Even though the chapter relies on trauma theory that is exclusively influenced by Western traumas, it seeks to adapt this theory to the understanding of a non-Western collective trauma experience. Moreover, an emphasis is placed on deploying psychoanalytical and historical writings on trauma to achieve an understanding of its literary aspect rather than using fiction to develop the pre-existing psychoanalytical and historical readings of trauma. Chapter Two, on the other hand, provides an application of the theoretical views presented in the preceding chapter. The second chapter explores the deployment of two particular literary devices – intertextuality and repetition – in the context of trauma narrative and how they re-create trauma in their own distinct way. Chapter Three focuses primarily on Farah’s characters and their problematic relationship with both the perception of time and memory-keeping. The chapter emphasizes that there is a complete identification between the teller of the memory and the memory told. This reading of Sweet and Sour Milk, Sardines and Close Sesame detangles the tension arising from the narrativisation of trauma from one end and the elements which engage in narrating it (language and characters) from the other.